Assessing the effects of climate variation and human activities on grassland degradation and restoration across the globe. (November 2019) - Liu, Yangyang; Zhang, Zhaoying; Tong, Linjing; Khalifa, Muhammad; Wang, Qian; Gang, Chengcheng; Wang, Zhenqian; Li, Jianlong; Sun, Zhengguo
Highlights: The relative contributions of climate variation and human activities on grassland degradation/restoration at the global scale were quantified. Climate and human factors contributed differently to grassland degradation/restoration among the studied six continents. Precipitation was the dominated climatic factor controlling grassland restoration in most areas during 2000–2013. The implementation of grassland protection policies in various countries is of great significance for grassland restoration. Abstract: While quantitative assessment of ecosystems degradation is quite addressed in the literature, quantitatively separating the relative contribution of climate variation and human activities to grassland ecosystem degradation is still limited, although well recognized as a key knowledge for a better understanding of the degradation mechanisms and for more efficient control of degradation processes. In this study, actual net primary productivity (ANPP) was selected as an indicator to investigate the grassland dynamics from 2000 to 2013. In addition, potential NPP (PNPP) and human-induced NPP (HNPP), which was calculated as the difference between PNPP and ANPP, were used to differentiate the relative impacts of climate variation and human activities on grassland degradation/restoration, respectively. Results showed that 60.94% of the total global area of grassland experienced restoration over the study period, with an increase in NPP by 1864.81 Tg C across the globe. The restored areas induced by climate variation and human activities accounted for 45.73% and 34.99% with an increases in NPP by 852.75 Tg C and 652.50 Tg C, respectively. By contrast, nearly 39.06% of the global grassland area experienced degradation. This degradation was associated with a noticeable decrease in ANPP by 325.53 Tg C. While 45.45% of the degraded grassland areas were influenced by climate variation, human activities were accounted for around 40.11% of this degradation. The relative effect of the two factors (i.e. climate variation and human activities) on grassland changes was found to vary greatly among the studied six continents. While human activities exerted larger impacts than climate variation on grassland degradation in North America and Europe, climate variation was the dominant factor for grassland restoration in Asia, Europe, Oceania and North America, which can be mainly attributed to the increase in precipitation during the study period. The findings of the current study improved our understanding of the relative impacts of climate variation and human activities on grassland degradation and restoration at the global scale.